2015
DOI: 10.1007/s11606-015-3209-6
|View full text |Cite
|
Sign up to set email alerts
|

Results from a Geographically Focused, Community-Based HCV Screening, Linkage-to-Care and Patient Navigation Program

Abstract: BACKGROUND: Many of the five million Americans chronically infected with hepatitis C (HCV) are unaware of their infection and are not in care. OBJECTIVE: We implemented and evaluated HCV screening and linkage-to-care interventions in a community setting. DESIGN: We developed a comprehensive, communitybased HCV screening and linkage-to-care program in a medically underserved neighborhood with high rates of HCV infection in Philadelphia, Pennsylvania. We provided patient navigation services to enroll uninsured p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 45 publications
4
82
1
Order By: Relevance
“…In an effort to expand HIV screening and care services in this urban community, this programme combined social marketing and community mobilization, door-to-door HIV and HCV outreach, and screening in non-clinical and clinical settings; the results of the screening and linkage to care programme have been presented elsewhere [17,27,28]. Among participants in the programme, we explored acceptability, affordability and attitudes about purchasing HIVSTs among participants.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to expand HIV screening and care services in this urban community, this programme combined social marketing and community mobilization, door-to-door HIV and HCV outreach, and screening in non-clinical and clinical settings; the results of the screening and linkage to care programme have been presented elsewhere [17,27,28]. Among participants in the programme, we explored acceptability, affordability and attitudes about purchasing HIVSTs among participants.…”
Section: Introductionmentioning
confidence: 99%
“…Additional strategies for improving linkage to and retention in care could be the use of patient navigators or care coordinators [80, 81]; however, the efficacy and effectiveness assessment of these interventions is still ongoing.…”
Section: Which Are the Perspectives For The Universal Screening Ofmentioning
confidence: 99%
“…31 Interventions to improve linkage to care have found that care coordination and patient navigator services are effective, but they cannot overcome barriers that include availability of specialty care and lack of health insurance coverage. 32,33 Treatment centers are not available in all geographic regions of the United States, and patients may be unable or unwilling to travel great distances. Project ECHO overcame many of these barriers by offering care in the rural communities of the patients.…”
Section: Linkage To Care and Treatment Programsmentioning
confidence: 99%